Development of an open-source toolbox for the analysis and visualization of remotely sensed time series - Blok, C.; Turdukulov, Ulanbek; Zurita-Milla, R.; Retsios, V.; Schouwenburg, M.; Metaferia, M. (2011)
The GEONETCast data-dissemination system delivers free multi-source raw satellite images and processed products to users worldwide; from these data, users can construct long time series to study dynamic phenomena. To explore these dynamics, using an animation with few controls is common practice. But animations easily produce information overload leading to change blindness, a problem that can be addressed in various ways. We present a combination of analytical and visual functionalities to better support visual exploration of animated time series. Analytical pre-processing functions include slicing and tracking of objects of interest. Results of the slicing and the tracking are input to the visualization environment, which is further enriched by tools to make various time, attribute, and area selections and by options to visually enhance selections relative to their surroundings, visualize the path of moving objects, and multiple layers. The resulting toolbox is dedicated to visual exploration and analysis of dynamic phenomena in time series. A case study demonstrates, with a use scenario, how it works. Early exposure of some visualization functions to users has already led to improvements, but more extensive testing will follow after further enrichment of the toolbox. Directions of future research are described.